A case of large leiomyoma arising from rudimentary horn in Mayer Rokitansky-Küster-Hauser syndrome, managed by minimally invasive surgery - Katkam, Rusheetha R.; Dalmia, Rachana D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome is a congenital disorder marked by aplasia or hypoplasia of the uterus and vagina as a result of arrest in the development of the müllerian ducts. Prevalence being 1 in 4000–5000 live births of females. Leiomyoma is the most common uterine tumor, their occurrence from rudimentary uterus in females with MRKH syndrome is very rare and only a few cases have been documented in the literature. Here we report a 38-year-old female, known case of MRKH syndrome presenting with USG suggestive of 7.9x7.4x6.0 leiomyoma in proximity to the hypoplastic uterus, undergoing a laparoscopic removal of fibroid with right ovarian cystectomy (incidental finding). Therefore, it is important to consider such unusual diagnosis of fibroids originating from primitive horns while treating these patients for gynecological symptoms as well as infertility, and consider them managing endoscopically.